Method for separating aluminosilicate minerals and purifying quartz sand under neutral condition and application thereof
By using a quartz inhibitor and aluminosilicate mineral collector under neutral conditions, the problem of difficult separation between quartz and aluminosilicate minerals in the prior art is solved, and an efficient and environmentally friendly quartz sand purification effect is achieved.
Patent Information
- Application Number
- CN202411650615.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-19
AI Technical Summary
The prior art faces the problems of equipment corrosion, environmental pollution, poor water solubility of collectors and unsatisfactory separation effect when separating quartz and aluminosilicate minerals, and cannot effectively deal with diversified aluminosilicate minerals.
The reverse flotation method under neutral conditions is adopted, and aluminosilicate mineral collector is added to efficiently separate quartz from aluminosilicate minerals.
The efficient separation of quartz and aluminosilicate minerals was achieved, the content of alumina was reduced to below 100 ppm, the purity of quartz sand was improved to more than 99.9%, and equipment corrosion and environmental pollution were avoided.
Smart Images

Figure QLYQS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high-purity quartz sand preparation, and in particular to a method for separating aluminosilicate minerals and purifying quartz sand under neutral conditions and application thereof. Background Art
[0002] High-purity quartz has excellent chemical stability, extremely low volume expansion coefficient, extremely high temperature resistance, high insulation and voltage resistance due to its unique molecular chain structure, lattice shape and lattice change law. It is an irreplaceable basic raw material in the fields of semiconductors, photovoltaics, optical fibers, and electric light sources, and occupies a pivotal position. It has been listed as a strategic non-metallic mineral, and its preparation and purification process is therefore of great research significance. In industrial production, deep purification and processing of quartz-rich ore is a conventional method for producing high-purity quartz with high economic value.
[0003] In natural quartz ore, there is often a type of aluminum silicate mineral. This type of mineral is very similar to the mineralogical structure of quartz. 4+ By Al 3+ The two are formed by substitution. This similar structure leads to similar physical and chemical properties between the two, which is not conducive to the purification and separation of minerals. In particular, when the aluminum content in quartz is too high, the properties of the corresponding quartz products in terms of photoelectric performance will be significantly reduced, which will in turn affect the quality of the quartz products. Therefore, it is necessary to strictly control the content of aluminum in the raw materials. Common aluminosilicate associated minerals mainly include feldspar, kaolin, zeolite, garnet, kyanite, sillimanite, mica, etc. In terms of separation and purification, aluminosilicate minerals other than mica are usually not dissolved or removed by high-concentration mixed acids (such as hydrofluoric acid and hydrochloric acid), nor are they magnetic and cannot be separated by magnetic separation. Therefore, achieving efficient separation of quartz and aluminosilicate minerals is a very challenging research task.
[0004] Flotation is a very efficient and economical mineral separation process in the deep processing of minerals. Using flotation to separate aluminosilicate minerals from quartz and then purify quartz is an effective strategy for preparing high-purity quartz sand. However, the existing flotation methods for separating quartz and aluminosilicate minerals face many problems: First, an acid or alkaline flotation environment is usually required, which often causes equipment corrosion, environmental pollution and even harm to operators; second, the commonly used collectors are poorly water-soluble (such as sodium oleate), and are easily precipitated from water during long-term storage, thereby affecting the amount of collector added, and the collectors used are often mixtures, and the interactions between them are relatively complex, which makes the industrial flotation effect unsatisfactory; third, the existing flotation schemes often only target one type of aluminosilicate minerals, such as the separation of feldspar and quartz, mica and quartz, etc., and lack systematic research on aluminosilicate minerals. In summary, the existing flotation schemes cannot meet the diverse needs in the field of high-purity quartz sand purification, so there is a real and urgent need to develop more efficient flotation methods for separating aluminosilicate minerals and quartz.
[0005] The patent specification with publication number CN108176518A discloses a neutral flotation method for purifying quartz minerals, which uses an alkali solution of amines, organic halogenated acids or halogenated acid salts as a mixture to separate iron oxide impregnated quartz sand and iron-containing aluminum silicate minerals in quartz sand, thereby obtaining high-purity quartz concentrate.
[0006] The patent specification with publication number CN110127708A discloses a method for purifying high-purity quartz sand with SiO2 purity ≥99.99%, including flotation, high-temperature activation and water quenching cooling, high-temperature alkali washing and impurity removal, high-temperature oxidation acid washing and impurity removal, etc. The flotation agents used in the flotation process are dodecylamine and its corresponding quaternary ammonium salt, No. 2 oil as a frother, and ethyl phenyl ester oil. Under the condition of pH 2.0~3.0, feldspar mineral impurities and layered aluminum silicate mineral particle impurities are floated out, thereby achieving the goal of purifying quartz sand.
[0007] In addition, there are some patented technologies that publicly report flotation separation methods for feldspar, mica and quartz respectively. However, these flotation separation methods are often only effective for some aluminosilicate minerals, and there is a lack of research on other aluminosilicate minerals such as kaolinite and zeolite. Summary of the invention
[0008] In view of the above technical problems and the shortcomings in the art, the present invention provides a method for separating aluminosilicate minerals and purifying quartz sand under neutral conditions and its application. The operation steps of the present invention are simple and efficient: a series of pretreatments can be performed on the quartz-containing raw ore to obtain quartz raw sand, and quartz reverse flotation can be performed under neutral and mild conditions, and a quartz inhibitor is preferentially added to inhibit the floating of quartz; then an aluminosilicate mineral collector is added to achieve efficient separation of quartz and aluminosilicate minerals; at the same time, in order to compensate for the weak foaming problem of the aluminosilicate mineral collector of the present invention, a foaming agent, preferably pine oil, needs to be added to extend the frothing time of flotation. The content of alumina in the quartz sand obtained after reverse flotation is reduced to below 100 ppm.
[0009] A method for separating aluminosilicate minerals and purifying quartz sand under neutral conditions, using one or more reverse flotation operations, the reverse flotation operation comprising: Add quartz inhibitor to the quartz raw sand slurry or the fine quartz sand slurry with low aluminum content obtained in the previous reverse flotation operation, and mix well; then add aluminum silicate mineral collector and mix well; then add frother under aeration stirring conditions to carry out quartz reverse flotation, during which stirring and scraping bubbles are maintained; after the reverse flotation is completed, wash the remaining slurry to obtain fine quartz sand with low aluminum content.
[0010] The raw quartz sand contains quartz and aluminosilicate minerals.
[0011] In the present invention, the aluminosilicate mineral may include one or more of feldspar, kaolin, zeolite, garnet, kyanite, sillimanite, and mica.
[0012] The particle size of the quartz raw sand in the quartz raw sand slurry can be 60-100 meshes.
[0013] In the raw quartz sand slurry, the mass concentration of raw quartz sand may be 45% to 55%.
[0014] In the said fine quartz sand slurry with low aluminum content, the mass concentration of the fine quartz sand with low aluminum content can be 45% to 55%.
[0015] The quartz raw sand can be obtained by pre-processing the raw ore, and the pre-processing may include: crushing, grinding, screening, magnetic separation, water washing, acid washing, and drying the raw ore in sequence.
[0016] In some embodiments, the crushing may include crushing the raw ore into small ores of 1 to 5 cm.
[0017] In some embodiments, the acid used for pickling may be 0.1 wt % to 1 wt % (eg, 0.5 wt %) dilute sulfuric acid.
[0018] In some embodiments, the mass content of quartz in the raw ore is not less than 50%, and the mass content of aluminosilicate minerals is not more than 50%.
[0019] During the reverse flotation operation, the pH of the slurry can be maintained at 6.5-7.5.
[0020] In the reverse flotation operation, no additional acid or alkali may be added.
[0021] During the reverse flotation operation, the slurry temperature can be maintained at 20-30°C.
[0022] The order of adding reagents during the reverse flotation operation of the present invention is crucial. In order to ensure the effective separation of quartz and aluminosilicate minerals, it is necessary to add a quartz inhibitor before adding a collector, thereby reducing the interaction between the collector and quartz and achieving the flotation separation of quartz and aluminosilicate minerals to the greatest extent.
[0023] The quartz inhibitor preferably includes one or both of sodium fluorosilicate and ammonium fluorosilicate.
[0024] The ratio of the added mass of the quartz inhibitor to the solid mass in the raw quartz sand slurry can be 15-20 g (grams): 1 t (ton).
[0025] The aluminosilicate mineral collector preferably includes one or more sulfonate zwitterionic collectors having the following structure: , Among them, n is selected from 6 to 16, for example, 6, 8, 10, 12, 14, 16, etc.
[0026] The aluminosilicate mineral collector of the present invention preferably adopts a zwitterionic compound containing a sulfonate group and a quaternary ammonium salt structure, wherein the zwitterionic compound structure comprises an anionic group sulfonate ion, a positively charged quaternary ammonium salt structure and a hydrophobic long-chain alkane, wherein the sulfonate ion and the quaternary ammonium salt structure are connected by three methylene groups, and the length of the long-chain alkane is eight to eighteen carbon structures.
[0027] Under neutral conditions, the surfaces of quartz and aluminosilicate minerals are negatively charged. The positively charged nitrogen ions in the zwitterionic compound collector used in the present invention are adsorbed on the surfaces of the two ores through electrostatic action; the aluminum ions in the aluminosilicate minerals are mutually adsorbed with the sulfonate groups in the collector through coordination action, and the adsorption of quartz on the collector is weak due to the lack of aluminum ions, thereby achieving selective adsorption of the collector on the aluminosilicate minerals, and then achieving highly selective flotation separation of the aluminosilicate minerals and quartz.
[0028] Further, the aluminosilicate mineral collector preferably includes one or more of 3-(N,N-dimethyldodecylammonium) propane sulfonate (CAS No.: 14933-08-5), hexadecyl sulfobetaine (CAS No.: 2281-11-0), 3-sulfobutyltetradecyldimethylbetaine (CAS No.: 14933-09-6), 3-(N,N-dimethyloctylammonium) propane-1-sulfonic acid inner salt (CAS No.: 15178-76-4), 3-(decyldimethylammonium) propane-1-sulfonate (CAS No.: 15163-36-7), and 3-(dimethyl(octadecyl)ammonium) propane-1-sulfonic acid inner salt (CAS No.: 13177-41-8).
[0029] In some preferred examples, the ratio of the added mass of the aluminosilicate mineral collector to the solid mass in the raw quartz sand slurry is 20-30 g:1 t. If the amount of collector added is too little, the separation effect of aluminosilicate minerals and quartz will be poor, affecting the quartz grade, while if the amount added is too much, part of the quartz sand will float up with the aluminosilicate minerals, affecting the quartz recovery rate.
[0030] In the present invention, in order to prolong the flotation time and improve the stability of the foam, a foaming agent needs to be added. The foaming agent preferably includes pine oil. The ratio of the added mass of the foaming agent to the solid mass in the raw quartz sand slurry can be 10-20 g:1 t.
[0031] The method of the present invention can obtain the low aluminum content fine quartz sand with SiO2 purity ≥ 99.9% and Al2O3 content ≤ 100 ppm by one or more reverse flotation operations. Multiple reverse flotation operations can further improve the purity of the product quartz sand.
[0032] The invention also provides application of the method in separating aluminosilicate minerals and purifying quartz sand.
[0033] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention adopts a reverse flotation strategy for ores with high quartz content, which is superior to the forward flotation strategy in reducing the amount of reagents used and improving the flotation separation effect.
[0034] (2) The preferred aluminosilicate mineral collector used in the present invention is a zwitterionic collector with a sulfonate group and a quaternary ammonium salt structure. The collector is synergistically adsorbed on different sites of aluminosilicate minerals by positively charged nitrogen ions and sulfonate anions, and has a stronger adsorption effect and a larger adsorption amount. Therefore, the collector has a greater ability to capture aluminosilicate minerals than traditional single or multiple mixed collectors. The effect of reverse flotation separation of quartz and aluminosilicate minerals by the collector is better than the flotation effect of using a single or mixed collector.
[0035] (3) The collector preferably used in the present invention has two polar groups and a long hydrophobic chain, and has good hydrophilicity and hydrophobicity, thus overcoming the problem of poor water solubility of the traditional collector with a single polar group. Compared with other collectors, the collector preferably used in the present invention has a stronger ability to capture aluminum and a higher sensitivity, and has a good ability to capture a small amount of aluminum exposed on the crystal surface, thereby showing a better separation effect in the flotation separation of quartz and aluminosilicate minerals.
[0036] (4) The reverse flotation process of the present invention is carried out under neutral conditions, avoiding the use of traditional strong acids and strong bases, thereby reducing the harm of the purification process to production equipment, ecological environment and operators. DETAILED DESCRIPTION
[0037] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only intended to illustrate the present invention and are not intended to limit the scope of the present invention. The operating methods in the following examples where no specific conditions are indicated are usually carried out under conventional conditions or under conditions recommended by the manufacturer. Example 1
[0038] 1. Mineral raw materials: The mass content of quartz in the original ore is 50.23%, the mass content of feldspar is 28.40%, the mass content of kaolin is 14.78%, and the mass content of other aluminum silicate minerals such as zeolite, garnet, kyanite and sillimanite is 4.32%. Phase analysis shows that the ore mainly contains quartz, feldspar and kaolin.
[0039] 2. Flotation reagents and operating conditions: Pretreatment process: Use a crusher to crush the above raw ore into 1-5 cm small ores, put the small ores into a wet mill for grinding, and screen out 60-100 mesh raw sand; then pour the screened raw sand into a magnetic separator for magnetic separation to remove magnetic impurities; the quartz sand after magnetic separation enters a scrubber and is washed with water. After the water washing is completed, 0.5wt% dilute sulfuric acid is used to clean the impurities on the surface of the ore sand, and then it is dried in a vacuum dryer after treatment.
[0040] Reverse flotation process: pour the raw sand obtained by pretreatment into the flotation machine, stir and rinse the preliminarily purified raw sand once with warm water at 20~30℃, and prepare it into raw sand slurry with a mass concentration of 45%~55%; add quartz inhibitor sodium fluorosilicate 20 g / t (t is based on the solid mass in the raw sand slurry, the same below) to the slurry, stir for 20 minutes, then continue to add aluminum silicate mineral collector 3-(N,N-dimethyldodecylammonium) propane sulfonate (CAS No.: 14933-08-5), 20 g / t (t is based on the solid mass in the raw sand slurry, the same below), stir for 30 minutes; add frother pine oil 10 g / t (t is based on the solid mass in the raw sand slurry, the same below) to the slurry under the condition of air stirring. g / t (t is the solid mass in the original sand pulp, the same below), the ore is subjected to quartz reverse flotation, the flotation is carried out for 30 minutes, during which stirring and scraping bubbles are carried out, and after the flotation is completed, the obtained quartz sand is rinsed two to three times with deionized water to clean the reagent residue on the surface of the mineral, and the above process is repeated once to obtain fine quartz sand. The pH of the pulp is always maintained at 6.5~7.5 during the reverse flotation process.
[0041] The test results show that the above process parameters and reagent conditions can effectively recover quartz minerals, with a recovery rate of 83.25%, and the product quartz sand with a grade (purity) of 99.95% is obtained, and the content of aluminosilicate minerals (alumina) is reduced to below 100 ppm. Example 2
[0042] 1. Mineral raw materials: The mass content of quartz in the original ore is 64.23%, the mass content of feldspar is 16.22%, the mass content of kaolin is 7.78%, the mass content of mica is 4.94%, and the mass content of other aluminum silicate minerals such as zeolite, garnet, kyanite and sillimanite is 3.86%. Phase analysis shows that the ore mainly contains quartz, feldspar, kaolin and mica.
[0043] 2. Flotation reagents and operating conditions: The pretreatment process is the same as in Example 1; Reverse flotation process: pour the raw sand obtained by pretreatment into the flotation machine, stir and rinse the preliminarily purified raw sand once with 20~30℃ warm water, and prepare it into raw sand slurry with a mass concentration of 45%~55%; add quartz inhibitor ammonium fluorosilicate 20 g / t to the slurry, stir for 20 minutes, then continue to add aluminum silicate mineral collector 3-(dimethyl (octadecyl) ammonium) propane-1-sulfonic acid inner salt (CAS No.: 13177-41-8) 30 g / t, stir for 30 minutes; add frother pine oil 10 g / t to the slurry under the condition of aeration and stirring, and perform quartz reverse flotation on the ore for 30 minutes, stir and scrape bubbles during the period, and rinse the obtained quartz sand with deionized water two to three times after flotation to clean the reagent residue on the surface of the mineral, and repeat the above process once to obtain fine quartz sand. During the reverse flotation process, the pH of the slurry is always maintained at 6.5~7.5.
[0044] The test results show that the above process parameters and reagent conditions can effectively recover quartz minerals, with a recovery rate of 80.11%, and the product quartz sand with a grade (purity) of 99.90% is obtained, and the content of aluminosilicate minerals (alumina) is reduced to below 100 ppm. Example 3
[0045] 1. Mineral raw materials: The mass content of quartz in the original ore is 78.19%, the mass content of feldspar is 8.26%, the mass content of garnet is 7.78%, and the mass content of other aluminum silicate minerals such as kaolin, zeolite, kyanite and sillimanite is 5.04%. Phase analysis shows that the ore mainly contains quartz, feldspar and garnet.
[0046] 2. Flotation reagents and operating conditions: The pretreatment process is the same as in Example 1; Reverse flotation process: pour the raw sand obtained by pretreatment into the flotation machine, stir and rinse the preliminarily purified raw sand once with 20~30℃ warm water, and prepare it into raw sand slurry with a mass concentration of 45%~55%; add quartz inhibitor ammonium fluorosilicate 10 g / t and sodium fluorosilicate 10 g / t to the slurry, stir for 20 minutes, then continue to add aluminum silicate mineral collector 3-sulfobutyl tetradecyl dimethyl betaine (CAS No.: 14933-09-6) 30 g / t, stir for 30 minutes; add frother pine oil 10 g / t to the slurry under the condition of aeration and stirring, and perform quartz reverse flotation on the ore for 30 minutes, stir and scrape bubbles during the period, and rinse the obtained quartz sand with deionized water two to three times after flotation to clean the reagent residue on the surface of the mineral, and repeat the above process once to obtain fine quartz sand. The pH of the slurry is always kept at 6.5~7.5 during the reverse flotation process.
[0047] The test results show that the above process parameters and reagent conditions can effectively recover quartz minerals, with a recovery rate of 82.21%, and the product quartz sand with a grade (purity) of 99.92% is obtained, and the content of aluminosilicate minerals (alumina) is reduced to below 100 ppm. Comparative Example 1
[0048] The difference between this comparative example and Example 1 is that sodium fluorosilicate, a quartz inhibitor, is not added to the flotation reagent, and the rest are the same.
[0049] The test results show that the absence of the quartz inhibitor sodium fluorosilicate not only significantly reduces the recovery rate of quartz to 61.29%, but also causes a slight decrease in the quartz grade, obtaining a product quartz sand with a grade of 99.93%, in which the content of aluminosilicate minerals (alumina) is reduced to below 100 ppm. Comparative Example 2
[0050] The only difference between this comparative example and Example 1 is that the quartz depressant added to the flotation reagent is 20 g / t of water glass (t is based on the solid mass in the original sand ore slurry), and the rest are the same.
[0051] The test results show that the replaced quartz inhibitor water glass has a poor effect on inhibiting quartz flotation under the neutral conditions of the present invention, wherein the quartz recovery rate is 71.68%, which is lower than the recovery rate when sodium fluorosilicate is used as an inhibitor, and only product quartz sand with a grade of 99.91% can be obtained, wherein the content of aluminosilicate minerals (alumina) is reduced to below 100 ppm. Comparative Example 3
[0052] The difference between this comparative example and Example 1 is that the collector is replaced with 30 g / t of trimethyl dodecyl ammonium chloride (t is based on the solid mass in the original sand ore slurry), and the rest are the same.
[0053] The test results show that the replaced collector trimethyldodecylammonium chloride cannot effectively separate quartz and aluminosilicate minerals under the neutral conditions of the present invention, wherein the quartz recovery rate is 87.32% and the grade is only 85.71%. The content of aluminosilicate minerals (alumina) exceeds 1%, and flotation cannot be carried out effectively. Comparative Example 4
[0054] The difference between this comparative example and Example 1 is that the collector is replaced by a mixed collector: a mixture of trimethyl dodecyl ammonium chloride and sodium dodecyl sulfate (in a mass ratio of 1:1), 30 g / t (t is based on the solid mass in the original sand ore slurry), and the rest are the same.
[0055] The test results show that the replaced mixed collectors trimethyl dodecyl ammonium chloride and sodium dodecyl sulfate will cause some aluminosilicate minerals to be unable to float under the neutral conditions of the present invention, and thus quartz and aluminosilicate minerals cannot be effectively separated. The quartz recovery rate is 94.39%, and the grade is only 79.12%. The content of aluminosilicate minerals (alumina) exceeds 2%, and flotation cannot be carried out effectively.
[0056] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. A method for separating aluminum silicate minerals and purifying quartz sand under neutral conditions, characterized in that: One or more reverse flotation operations are used, wherein the reverse flotation operations include: Add quartz inhibitor to the quartz raw sand slurry or the fine quartz sand slurry with low aluminum content obtained in the previous reverse flotation operation, and mix well; then add aluminum silicate mineral collector and mix well; then add frother under aeration stirring conditions to carry out quartz reverse flotation, during which stirring and scraping bubbles are maintained; after the reverse flotation is completed, wash the remaining slurry to obtain fine quartz sand with low aluminum content.
2. The method according to claim 1, characterized in that The raw quartz sand contains quartz and aluminosilicate minerals; The quartz sand in the quartz sand slurry has a particle size of 60-100 meshes; In the quartz raw sand slurry, the mass concentration of quartz raw sand is 45% to 55%; In the said fine quartz sand slurry with low aluminum content, the mass concentration of the fine quartz sand with low aluminum content is 45% to 55%; The quartz raw sand is obtained by pre-processing the raw ore, and the pre-processing includes: crushing, grinding, screening, magnetic separation, water washing, acid washing and drying the raw ore in sequence; The crushing includes crushing the raw ore into small ores of 1 to 5 cm; The acid used in the pickling is 0.1wt%~1wt% dilute sulfuric acid; The mass content of quartz in the raw ore is not less than 50%, and the mass content of aluminosilicate minerals is not more than 50%; The aluminosilicate minerals include one or more of feldspar, kaolin, zeolite, garnet, kyanite, sillimanite and mica.
3. The method according to claim 1, characterized in that In the reverse flotation operation: The pH of the slurry is maintained at 6.5~7.5; No additional acid or base is added; The slurry temperature is maintained at 20~30℃.
4. The method according to claim 1, characterized in that: The quartz inhibitor includes one or both of sodium fluorosilicate and ammonium fluorosilicate; The ratio of the added mass of the quartz inhibitor to the solid mass in the raw quartz sand slurry is 15-20 g:1 t.
5. The method according to claim 1, characterized in that The aluminosilicate mineral collector includes one or more sulfonate zwitterionic collectors having the following structure: , Among them, n is selected from 6 to 16.
6. The method according to claim 5, characterized in that The aluminosilicate mineral collector includes one or more of 3-(N,N-dimethyldodecylammonium) propane sulfonate, hexadecyl sulfobetaine, 3-sulfobutyltetradecyldimethylbetaine, 3-(N,N-dimethyloctylammonium) propane-1-sulfonic acid inner salt, 3-(decyldimethylammonium) propane-1-sulfonate, and 3-(dimethyl(octadecyl)ammonium) propane-1-sulfonic acid inner salt.
7. The method according to claim 1, 5 or 6, characterized in that: The ratio of the added mass of the aluminosilicate mineral collector to the solid mass in the raw quartz sand slurry is 20-30 g:1 t.
8. The method according to claim 1, characterized in that The foaming agent includes pine oil; The ratio of the added mass of the foaming agent to the solid mass in the raw quartz sand slurry is 10-20 g:1 t.
9. The method according to claim 1, characterized in that: The purity of SiO2 in the fine quartz sand with low aluminum content obtained by one or more reverse flotation operations is ≥99.9%, and the content of Al2O3 is ≤100 ppm.
10. Use of the method according to any one of claims 1 to 9 in separating aluminosilicate minerals and purifying quartz sand.
Citation Information
Patent Citations
Purification method of high-purity quartz sand with SiO2 purity more than or equal to 99.99%
CN110127708A
Method of microorganism induction bauxite flotation desilicication
CN104525381A
Cassiterite flotation collecting agent and application thereof
CN106861919A
Preparation method of neutral flotation agent for purifying quartz minerals
CN108176518A
Preparation method of high-purity quartz sand
CN110665631A
Cited By
Method for preparing high-purity quartz sand through reverse flotation
CN121063544A